2018
DOI: 10.1539/joh.17-0146-oa
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative DNA damage in cultured macrophages exposed to indium oxide

Abstract: Objectives: Indium compounds are used in manufacturing displays of mobile phones and televisions. However, these materials cause interstitial pneumonia in exposed workers. Animal experiments demonstrated that indium compounds caused lung cancer. Chronic inflammation is considered to play a role in lung carcinogenesis and fibrosis induced by particulate matters. 8-Nitroguanine (8-nitroG) is a mutagenic DNA lesion formed during inflammation and may participate in carcinogenesis. To clarify the mechanism of carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(58 reference statements)
0
7
0
3
Order By: Relevance
“…In a collaboration with Khon Kaen University, Thailand, we firstly reported 8-nitroguanine and 8-oxodG formation in the livers of hamsters treated orally with the liver fluke in an animal model for OV-related cholangiocarcinoma [ 4 ]. In our previous studies based on DNA lesions, we investigated the molecular mechanisms of cancers due to infection (e.g., OV-related cholangiocarcinoma [ 2 , 4 6 ], Schistosoma haematobium -associated bladder cancer [ 7 , 8 ], Helicobacter pylori -infected gastric cancer [ 9 ], human papillomavirus-related cervical cancer [ 10 ], Epstein-Barr (EB) virus-infected nasopharyngeal carcinoma [ 11 ]), and pro-inflammatory factors (e.g., asbestos [ 12 , 13 ], nanomaterials [ 14 17 ], and inflammatory diseases such as Barrett’s esophagus [ 18 , 19 ], and oral leukoplakia [ 20 ]). In addition, inflammation plays a role in the epigenetic alterations in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a collaboration with Khon Kaen University, Thailand, we firstly reported 8-nitroguanine and 8-oxodG formation in the livers of hamsters treated orally with the liver fluke in an animal model for OV-related cholangiocarcinoma [ 4 ]. In our previous studies based on DNA lesions, we investigated the molecular mechanisms of cancers due to infection (e.g., OV-related cholangiocarcinoma [ 2 , 4 6 ], Schistosoma haematobium -associated bladder cancer [ 7 , 8 ], Helicobacter pylori -infected gastric cancer [ 9 ], human papillomavirus-related cervical cancer [ 10 ], Epstein-Barr (EB) virus-infected nasopharyngeal carcinoma [ 11 ]), and pro-inflammatory factors (e.g., asbestos [ 12 , 13 ], nanomaterials [ 14 17 ], and inflammatory diseases such as Barrett’s esophagus [ 18 , 19 ], and oral leukoplakia [ 20 ]). In addition, inflammation plays a role in the epigenetic alterations in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that 8-nitroG was formed at the sites of inflammation-related carcinogenesis in various animal model and clinical specimens 20,40,41 . Our studies using cultured cells have shown that particulate materials, including MWCNT 27,28 , carbon black 29 and In 2 O 3 21 , induced 8-nitroG formation. Because the glycosidic bond between 8-nitroG and deoxyribose is chemically unstable, 8-nitroG can be spontaneously released from DNA, resulting in the formation of apurinic site 42 .…”
Section: Discussionmentioning
confidence: 80%
“…The objective of this study was to determine the genotoxic effects of indium compounds on lung epithelial cells, and clarify the molecular mechanism. We have recently reported that In 2 O 3 induced 8-nitroG formation in mouse macrophages 21 . In this study, we used In 2 O 3 and ITO nanoparticles as representative indium compounds to examine 8-nitroG formation in human lung epithelial cells.…”
mentioning
confidence: 94%
“…5 Mouse macrophages with indium oxide in vitro suggested that endocytosis and NO generation participate in indium-induced 8-nitroguanine (a mutagenic DNA lesion formed during inflammation formation). 15 These results suggest that inhalation of indium compounds, causing pulmonary inflammation associated with oxidative stress, endocytosis, and NO released from indium-exposed inflammatory cells, may induce DNA damage in adjacent lung epithelial cells and contribute to carcinogenesis. However, the development of interstitial fibrotic changes and its relationship with the carcinogenesis needs to be further explored.…”
Section: Discussionmentioning
confidence: 87%
“…InP inhalation demonstrated the development of oxidative stress, identified by elevated levels of inducible nitric oxide synthase, cyclooxygenase‐2, glutathione‐S‐transferase Pi, and 8‐hydroxydeoxyguanosine, resulting in pulmonary inflammation in progression to atypical hyperplasia and lung cancer . Mouse macrophages with indium oxide in vitro suggested that endocytosis and NO generation participate in indium‐induced 8‐nitroguanine (a mutagenic DNA lesion formed during inflammation formation) . These results suggest that inhalation of indium compounds, causing pulmonary inflammation associated with oxidative stress, endocytosis, and NO released from indium‐exposed inflammatory cells, may induce DNA damage in adjacent lung epithelial cells and contribute to carcinogenesis.…”
Section: Discussionmentioning
confidence: 94%